(untitled) (Journal of Educational Management, 2014)
This paper presents the findings of a study that explored how authorities of Cape Coast perceive the role of mass media in corporate communication and reputation management. The study which was descriptive by design, solicited information from 77 purposively selected senior members in the university. Simple quantitative methods involving frequency tables, percentages, bar and pie charts were employed in analyzing the data collected. Among other findings, the study found that the University had adopted the use of multiple media especially radio, television, internet and newspaper to communicate to students, staff the University Community and its large external publics. The university’s use of media is however mostly uncoordinated. Based on the findings, the paper argues that the University can study that explored how authorities of maximise benefit of the use of mass media if it adequately resources and positions its Division of Public Affairs to enable it enhance its performance and also educate the University Community on the role of media in corporate affairs.